Containerized Event-Driven Microservice Architecture - Siti Zulaikha Mohd Zuki; Radziah Mohamad; Nor Azizah Saadon (مجلة بغداد للعلوم, 2024)
Microservice architecture offers many advantages, especially for business applications, due to its flexibility, expandability, and loosely coupled structure for ease of maintenance. However, there are several disadvantages that stem from the features of microservices, such as the fact that microservices are independent in nature can hinder meaningful communication and make data synchronization more challenging. This paper addresses the issues by proposing a containerized microservices in an asynchronous event-driven architecture. This architecture encloses microservices in containers and implements an event manager to keep track of all the events in an event log to reduce errors in the application. Experiment results show a decline in response time compared to two other benchmark architectures, as well as a lessening in error rate.